2017
DOI: 10.1002/2016jd026369
|View full text |Cite
|
Sign up to set email alerts
|

On the upward flux of sea‐spray spume droplets in high‐wind conditions

Abstract: It has been speculated that the spume droplets torn off from ocean waves in high wind speeds (larger than about 9 m s−1) enhance air‐sea fluxes. However, the vertical transport of spume droplets in the high‐wind atmospheric boundary layer (ABL) is little researched and lacks the support of numerical simulations. Based on observational data and the characteristics of high‐wind ABL above the ocean, the vertical transport of spume droplets is studied and simulated. It is revealed that the existence of gusty wind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Previous assumption to exclude coarse mode sea salt with r d > 10 μm is that it settles too quickly after emitted from ocean surface. However, new observation data shows that strong wind is generally accompanied by positive vertical velocity and coherent gusts, which enable some of large sea salt particles to rise into atmospheric boundary layer (Wu et al, ). The new scheme is based on Andreas () by including an uplifting factor k up based on the work of Wu et al ().…”
Section: Summary and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous assumption to exclude coarse mode sea salt with r d > 10 μm is that it settles too quickly after emitted from ocean surface. However, new observation data shows that strong wind is generally accompanied by positive vertical velocity and coherent gusts, which enable some of large sea salt particles to rise into atmospheric boundary layer (Wu et al, ). The new scheme is based on Andreas () by including an uplifting factor k up based on the work of Wu et al ().…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Moreover, Cheng et al () found that strong winds are always accompanied with positive upward vertical velocity and large amplitude gusts in the marine‐atmospheric boundary layer. They can pick up some of the emitted large droplets into marine boundary layer (Wu et al, ).…”
Section: Model and Methodsmentioning
confidence: 99%
See 3 more Smart Citations